ARE LARGE INNOVATIVE FIRMS MORE EFFICIENT? - SÁNCHEZ-PÉREZ, Rosario; DÍAZ-MAYANS, M. Ángeles (Theoretical and Practical Research in Economic Fields; Vol 4 No 1 (2013): TPREF, Volume IV, Issue 1(7), Summer 2013, 2013)
Size is one of the factors that condition the managerial organization of the firms and their efficiency and productivity. Moreover size has been found a highly significant variable in explaining differences in firm’s innovative activities and the returns of R&D expenditures, and it is a well-established connection between productivity and innovative activities . This paper analyses the relationship between innovative activities and size and their effect over firms’ technical efficiency and then over their productivity. The analysis takes, also, into account other variables that could affect the relationship between productivity and innovative activities: industrial sector, market structure, or firms’ financial conditions. We use a micro panel data set of Spanish manufacturing firms, during the period 2004–2009, to simultaneously estimate a stochastic frontier production function and the inefficiency determinants. The data source is published in the Spanish Industrial Survey on Business Strategies (Encuesta sobre Estrategias Empresariales, ESEE), collected by the Fundación SEPI. Our results show that innovative firms are more efficient than non-innovative firms; and that small and medium-sized firms’ tent to be more efficient than large firms are.